DEVELOPMENT AND CHARACTERIZATION OF COMPRITOL ATO® BASE IN NANOSTRUCTURED LIPID CARRIERS FORMULATION WITH THE PROBE SONICATION METHOD - JAFAR, GARNADI; SALSABILLA, SYIFA; SANTOSO, RAHMAT (International Journal of Applied Pharmaceutics, 2022)
Objective: Vitamin E acetate has antioxidant activity that can prevent premature aging of the skin, but it is highly lipophilic (log p±12.2) and potentially degraded. To overcome the permeability and stability problems, the vitamin E acetate needs to be developed in Nanostructured Lipid Carrier (NLC), a nano-delivery system based on solid lipid and liquid lipid that is stabilized by surfactants as a colloidal system. Methods: The formulation of vitamin E acetate into NLC was carried out using hot homogenization method and then sonicated using a probe sonicator. The materials used were vitamin E acetate 2%, Compritol® 2-6%, Myritol® 1%, and Plantacare® 1-3%. The results of the NLC were then characterized by measuring the particle size, zeta potential, polydispersity index, entrapment efficiency, and its morphology. Results: The results of characterization showed that NLC of vitamin E acetate has 280-375 nm particle size, the zeta potential was-23 mV to-28 mV, the polydispersity index was<0.5, the entrapment efficiency was 92-97%, and the morphological results was in the form of a spherical shape. Conclusion: The results show that the Nanosturctured Lipid Carriers of vitamin E acetate shows good results.